Circular bioeconomy in strawberry cultivation: phytochemicals in fruits and leaves, and yield potential of seven genotypes - Chiomento, José Luís Trevizan; De Nardi, Fabiola Stockmans; Grando, Luiza Alessandra; Trentin, Thomas Dos Santos; Anzolin, Jéfferson; Albrecht, Gustavo Eduardo; Huzar-Novakowiski, Jaqueline; Basílio, Letícia Silva Pereira [UNESP]; Monteiro, Gean Charles [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (FapUNIFESP (SciELO), 2024)
Seven strawberry genotypes were analyzed in order to differentiate fruit production and quality. The discarded leaves (by-product) were also used to characterize their phytochemical profile with a view to potential use in the pharmaceutical and agricultural industries. The multivariate analysis gave rise to heterogeneous groups among the seven genotypes. ‘Fronteras’ and ‘Monterey’ were the most productive. ‘Camino Real’ produced fruits with the highest polyphenols concentrations. ‘Fronteras’ produced leaves with the best phytochemical profile and, together with ‘Camino Real’, the highest antioxidant activity. The genotypes differ in terms of the yield and fruit, and leaf phytochemical profiles. ‘Camino Real’ can be used to optimize and market all the organs produced (fruits and leaves) and ‘Fronteras’ to increase the fruit yield and the use of leaves as a cultivation by-product.
Keywords: biomolecules; by-product; Fragaria X ananassa Duch; greenhouse; substrate